Glass fiber reinforced sealants for solid oxide fuel cells - Timurkutluk, Bora; Altan, Tolga; Celik, Selahattin; Timurkutluk, Cigdem; Palaci, Yuksel (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
Novel sealants for solid oxide fuel cells are developed by addition of glass fiber into glass ceramic as a reinforcement material. Various sealants including three different fiberglass types and four different structural designs are fabricated. The mechanical and sealing performances of the sealants are investigated via tensile and short stack leakage tests, respectively. The tensile tests reveal that the fracture strength of the sealants varies depending on the type and number of the glass fiber used. In general, the sealants having relatively high number of glass fiber layers exhibit relatively low joining strength. The best bonding strength values are obtained from the sealants having a structure where a single glass fiber layer is sandwiched between two glass-ceramic layers. The sealing performance tests are performed for the sealants showing the highest and lowest fracture strengths in the tensile tests as well as for the sealant without glass fiber addition as a base case for a comparison. The results indicate that it is possible to obtain a gas-tight sealing at high temperatures under all pressures studied, whereas leakage occurs at room temperature for all cases considered. However, the sealing performance is found to be related with the mechanical strength of the sealants. (C) 2019 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Solid oxide fuel cell; Sealant; Glass-ceramic; Glass fiber; Tensile tests; Sealing performance; CERAMIC SEALANT; SEALING GLASS; CRYSTALLIZATION KINETICS; CHEMICAL-STABILITY; COMPRESSIVE SEALS; LEAKAGE TESTS; SOFC; OPTIMIZATION; ELECTROLYTE; PERFORMANCE; Chemistry; Electrochemistry; Energy & Fuels